Penggunaan Metode AHP (Analytical Hierarchy Process) Dalam Sistem Penunjang Keputusan: Systematic Literatur Riview - Muhamad Rizky (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
Decision support systems can be used to help determine a decision. One of the methods used is the AHP (Analytical Hierarchy Process) method which is considered a flexible method and suitable for decision making. The purpose of this research is to see the use of the Analytical Hierarchy Process (AHP) method in a decision support system to assist a decision. This research method is literature study. The results of this research are that the AHP method in decision support systems can be used as a method of choice that can help determine decisions in various sectors of life.